The metalloproteinase ADAMDEC1 maintains a novel growth factor signalling loop in glioblastoma cancer stem cells. (12th October 2019) - Jimenez-Pascual, Ana; Hale, James; Kordowski, Anja; Pugh, Jamie; Rao, Shilpa; Silver, Daniel; Alban, Tyler; Watson, Defne; Chen, Rui; McIntyre, Thomas; Colombo, Giorgio; Taraboletti, Giulia; et al.
Abstract: Glioblastomas (GBM) are lethal brain tumours where poor outcome is attributed to cellular heterogeneity, therapeutic resistance, and a highly infiltrative nature. These characteristics are preferentially linked to GBM cancer stem cells (GSCs), but how GSCs maintain their stemness is incompletely understood and the subject of intense investigation. Here, we identify a novel growth factor signalling loop that induces and maintains GSCs. This loop consists of an atypical metalloproteinase, a disintegrin and metalloproteinase domain-like protein decysin 1 (ADAMDEC1), secreted by GSCs. ADAMDEC1 solubilizes fibroblast growth factor-2 (FGF2) in the tumour microenvironment. We find that GSCs exclusively express FGF receptor 1 (FGFR1), which upon binding of FGF2 induces upregulation of Zinc finger E-box-binding homeobox 1 (ZEB1). ZEB1 is a regulator of stemness and tumour initiation, and therefore ADAMDEC1-FGF2-FGFR1 signalling promotes malignancy in GBM. We further show that ZEB1 regulates ADAMDEC1 expression, creating a positive feedback loop. Genetic or pharmacological targeting of components of this axis attenuates self-renewal and tumour growth. These findings reveal a new signalling axis for GSC maintenance and highlight ADAMDEC1 and FGFR1 as potential therapeutic targets in GBM.